IMPACT OF TEMPERATURE CHANGE ON GROWTH OF LABEO ROHITA: DEVELOPMENT OF A GROWTH MODEL - DAS, M. K.; SRIVASTAVA, P. K.; DEY, S.; MONDAL, MD. L.; MUKHOPADHYAY, M. K.; SAHA, P. K. (Journal of the Inland Fisheries Society of India, 2021)
Enhanced temperature is one of the most important drivers of climate change as evidenced by a perceptible rise of air and water temperature in various regions of India. Unit rise in water temperature affect the physiological features of freshwater fish in aquaculture. Investigations were conducted to assess the impact of increasing water temperature of 29 ºC, 30 ºC, 31 ºC, 32 ºC, 33 ºC, 34 ºC and 35 ºC on the growth, Labeo rohita fingerlings reared for five weeks in aquarium. The fishes were fed pelletised feed ad libitum. Fish reared at 34 ºC water temperature exhibited significantly (P